Colonial Migrants: Recent Work on Puerto Ricans on and off the Island - Jorge Duany (NWIG, 2008)
[First paragraph]
Colonial Subjects: Puerto Ricans in a Global Perspective. Ramón Grosfoguel. Berkeley: University of California Press, 2003. xi + 268 pp. (Paper US $ 21.95)
Boricuas in Gotham: Puerto Ricans in the Making of Modern New York City. Gabriel Haslip-Viera, Angelo Falcón & Félix Matos Rodríguez (eds.). Princeton NJ: Markus Wiener Publishers, 2004. viii + 240 pp. (PaperUS $ 24.95)

Recent studies of Puerto Ricans have revisited their colonial status, national identity, and transnational migration from various standpoints, including postcolonial, transnational, postmodern, queer, and cultural studies.1 Most scholars in the social sciences and the humanities no longer question whether Puerto Rico is a colony of the United States. What is often discussed, sometimes angrily, is the exact nature of U.S. colonialism, the extent to which the Island has acquired certain “postcolonial” traits such as linguistic and cultural autonomy, and the possibility of waging an effective decolonization process. The issue of national identity in Puerto Rico is still contested as intensely as ever. What is new about current scholarly discussions is that many intellectuals, especially those who align themselves with postmodernism, are highly critical of nationalist discourses. Other debates focus on the appropriate approach to population movements between the Island and the U.S. mainland. For example, some outside observers insist that, technically speaking, the Puerto Rican exodus should be considered an internal, not international, migration, while others, including myself, refer to such a massive dispersal of people as transnational or diasporic. Much of this1. D uany 2002; Pabón 2002; Martínez-San Miguel 2003; Ramos-Zayas 2003; Rivera 2003; Negrón-Muntaner 2004; Pérez 2004. controversy centers on whether the geopolitical “border” between the Island and the mainland is equivalent to a national “frontier” in the experiences of Puerto Rican migrants.